Advances in Radiation/Photon therapy technology for the treatment of brain metastases - Hui Wang; Jing Chu; Yao Ren; Wenfan Deng; Lidan Zhang; Lijuan Shen; Yu Kuang; Lixia Xu (Journal of Innovative Optical Health Sciences)
With advancements in systemic therapy, the incidence of brain metastases (BMs) continues to rise, leading to severe neurological complications. Effective and precise treatment modalities are, therefore, critically important for managing BMs. Radiation therapy (RT), including photon therapy, has been essential in managing BMs. Recent technological advances have significantly enhanced the precision, efficacy, and safety of these treatments. This comprehensive review provides an in-depth examination of the latest advancements in radiation and photon therapy technologies for treating BMs, focusing on innovations such as stereotactic radiosurgery (SRS), whole-brain radiation therapy (WBRT), laser interstitial thermal therapy (LITT), and other radiation-related treatment modalities. Additionally, we discuss clinical outcomes, challenges, and future directions in this rapidly evolving field. While a detailed comparison of techniques is beyond the scope of this paper, this paper provides up-to-date technical information for physicians, medical physicists, patients, and researchers in related fields, potentially enhancing clinical outcomes. Among the treatment modalities, SRS has become a cornerstone of RT for BMs, with its implementation spanning multiple modalities over the past few decades. Given its inherent minimally invasive nature and growing clinical acceptance, SRS is positioned to further evolve as a key therapeutic tool in both neurosurgery and radiotherapy.